(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-3-70-77 The linguistic means of creating a language game in French advertising texts at the phonetic, lexical, word-formation, grammatical levels of the language are investigated. Homophones and paronyms are distinguished on the phonetic level, stylistic tropes – on the lexical, stylistic figures – on the grammatical, contamination – on the word-formation. Cases of combinations of different tropes and figures in some advertising texts are established. Key words: language game, advertising discourse, advertising text, linguistic means, language level, homophones, paronyms, stylistic tropes, stylistic figures